Implementing FT-CORBA with Portable Interceptors: Lessons Learned - Greve, Fabíola; Le Narzul, Jean-Pierre (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2002: Anais do III Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2002.23404, 2002)
In this paper, we present the design of Open EDEN, an implementation of the FT-CORBA specification based on the use of a group communication framework, called EDEN. The design of Open EDEN was driven by the desire to use only portable techniques (mainly portable interceptors) to integrate the EDEN framework within a CORBA platform. We discuss the main difficulties we encountered and we draw some conclusions about the adequacy of this choice.